2017
DOI: 10.1128/mbio.00511-17
|View full text |Cite
|
Sign up to set email alerts
|

Novel Chromosome Organization Pattern in Actinomycetales —Overlapping Replication Cycles Combined with Diploidy

Abstract: Bacteria regulate chromosome replication and segregation tightly with cell division to ensure faithful segregation of DNA to daughter generations. The underlying mechanisms have been addressed in several model species. It became apparent that bacteria have evolved quite different strategies to regulate DNA segregation and chromosomal organization. We have investigated here how the actinobacterium Corynebacterium glutamicum organizes chromosome segregation and DNA replication. Unexpectedly, we found that C. glu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 93 publications
4
28
1
Order By: Relevance
“…Recent work showed that M. smegmatis compensates for its elongated replication time (more than 2 h) by initiating chromosome replication before cytokinesis (26) and having a relatively large fraction of cells (up to 15%) undergoing multifork chromosome replication (28). In this, M. smegmatis resembles other actinobacterial species, such as Corynebacterium glutamicum (54). Our experiments revealed that, in mycobacteria, the initiation of the next replication round and the start of septum formation precede sister chromosome separation by ϳ20 min and 40 min, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work showed that M. smegmatis compensates for its elongated replication time (more than 2 h) by initiating chromosome replication before cytokinesis (26) and having a relatively large fraction of cells (up to 15%) undergoing multifork chromosome replication (28). In this, M. smegmatis resembles other actinobacterial species, such as Corynebacterium glutamicum (54). Our experiments revealed that, in mycobacteria, the initiation of the next replication round and the start of septum formation precede sister chromosome separation by ϳ20 min and 40 min, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, cellular localization of fluorescent ParB-eYFP foci is similar to wild type, positioning at cell poles and migrating to the newly formed septa (Fig. 2B, S3) 40 . Interestingly, the combination of a single parS site with ParB-eYFP resulted in 7% anucleoid mini-cells (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…Previous studies on C. glutamicum chromosome partitioning have revealed two stable ParB- oriC clusters at each cell pole, while newly replicated origins are segregated towards a division septa formed at midcell 40 . In B. subtilis , C. crescentus and P. aeruginosa ParAB-mediated chromosome segregation and folding depends on parS sites 18,19,21 .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations